Material selection for automated dry fiber placement using the analytical hierarchy process - Laura Veldenz (Taylor & Francis Group, 2018)
Dry fiber tapes have become an alternative to pre-impregnated tapes for automated fiber placement. However, their industrial adoption is inhibited by high upfront research and development cost. To reduce the cost of material selection as part of such an investment, this work presents the application of the analytical hierarchy process (AHP) to material selection with a focus on material processability and manufacturing quality. The selection is based on procurement, material and its performance throughout the manufacturing process, and some laminate quality indicators. Criteria and sub-criteria were identified and implemented into the AHP. This established decision making tool was compared to a more efficient derivative using the chain of interaction method. Two materials, including the selected material, were used to manufacture a small-scale L-section composite component. This demonstrates that the proposed material selection method predicted the more preferable material for manufacturing quality when applied to a complex geometry.